Hubungan Parenting Self Efficacy dengan Work Family Conflict pada Perawat di Kota Bukittinggi - Widya Astuti; Zulian Fikry (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to investigate the relationship between Parenting Self-Efficacy and Work-Family Conflict among nurses in Bukittinggi City. Parenting Self-Efficacy refers to the belief of parents in their ability to successfully carry out caregiving roles, while Work-Family Conflict is defined as a condition of role conflict that arises when the demands of work and family interfere with one another, thereby disrupting role balance. Nurses are one of the professions highly vulnerable to experiencing work-family conflict due to the demands of shift work, workload, and responsibilities at home, particularly for those who are married and have children. This research employed a quantitative approach with a correlational design to examine the direction and strength of the relationship between the two variables. The participants consisted of 85 nurses working in Bukittinggi City, selected using purposive sampling with specific criteria, namely being married, having children, and having a minimum of three years of work experience. Data were collected using standardized instruments in the form of the Parenting Self-Efficacy Scale and the Work-Family Conflict Scale, both of which had previously undergone adaptation and validity testing. The data were analyzed using Pearson correlation analysis to determine the relationship between the two variables. The results showed a significant negative relationship between Parenting Self-Efficacy and Work-Family Conflict (r = -0.400, p < 0.01). This finding indicates that nurses with higher levels of Parenting Self-Efficacy tend to experience lower levels of Work-Family Conflict, and conversely, those with lower self-efficacy in parenting are more likely to encounter greater conflicts between work and family roles. These findings highlight the importance of strengthening Parenting Self-Efficacy as a strategy to help nurses manage dual-role demands more effectively.